Analysis of Three Synthese Signals and Roads at Jl. Raya Karang Satria - Bekasi District - Dermawan, Widodo Budi; Anwardi, Putri Oktavian (Journal of World Conference (JWC), 2020)
Bekasi Regency is a Regency in West Java Province with a population of ± 3,500,023 Million People (Statistics Indonesia, 2017). Jl. Raya Karang Satria - Bekasi Regency is access to the main road to the city border, besides that access to residential locations, schools, which makes vehicle traffic especially during rush hour more congested by the activities on the side of the road such as the ups and downs of passengers from public transportation, as well as vehicles that stop causing long vehicle queues and can reduce travel time. To get primary data that is by surveying traffic volumes, geometric conditions, and environmental conditions. While secondary data obtained by searching using internet media. The analysis data used is guided by the Indonesian Road Capacity Manual Method (MKJI 1997). With this method, the capacity, degree of saturation, delay, and service level at the intersection can be known. From the results of the study obtained the largest degree of saturation (DS) value of 0.95 pcu / hour means that the value exceeds that required by MKJI (1997) which is <0.75 from the result of the average intersection delay (D intersection) of the largest 17 sec / pcu. This shows that the level of intersection C service is unstable flow because it has limited speed and movement and therefore it is necessary to review the level of intersection service. And researchers provide an alternative to improve the performance of these unsignalized intersections by changing FRSU from 0.98 to 1 and prohibiting right-turn traffic from both Major D to Minor C and from Minor C to Major B and removing side obstacles. For the road section, the highest degree of saturation (DS) value is obtained 0.74. This shows that the level of segment service is not stable. So an alternative is done to improve the level of segment performance by removing the original side obstacle factor of 0.86 to 1 on each arm.